STUDY OF THE EFFECT OF CRUDE EXTRACTS OF Sonchus oleraceus ON CANCER CELL GROWTH (In vivo): Zeinab R.Zgheir ,Nahi Y. Yaseen , Talib A. Makkawi - Zgheir, Zeinab R. (The Iraqi Journal of Veterinary Medicine, 2010)
The in vivo study was designed to evaluate the anticancer effects of these three types of the extracts on the AM-3 (Murine mammary adenocarcinoma). The LD50 was (5 g/kg, 6 g/kg and 8 g/kg) for ethanolic, hot aqueous and cold aqueous extracts respectively. The therapeutic doses of extracts were daily injected subcutaneously for two weeks, three weeks and four weeks. The histopathological study revealed pathological changes in some organs; the group that treated with ethanolic extract showed sever deposition of amyloid in some organs like spleen. The blood vessel filled with inflammatory cells as neutrophiles and cells infiltration in the lung tissue. Hot and cold aqueous extracts showed inflammatory mononuclear cells infiltration in the kidney and lung, section with necrosis in most of the cancer cells in the lung tissue; with few necrotic changes in the normal tissue were noticed after one month of treatment by hot and cold aqueous extracts.